An experimental study of fire development under varying ventilation conditions during the depressurization process in pressurized buildings - Kaiqiang Wang; Zhigang Shang; Weijun Liu; Kang Wen; Jun Zhang; Bin Yao; Weiguo Song (Journal of Safety Science and Resilience)
Hermetic pressurized buildings are a new type of building in high-altitude areas that efficiently addresses issues such as high-altitude reactions. The indoor pressure is higher than the external pressure under working conditions, and pressure relief must be carried out first during emergencies. The emergency pressure relief process during a fire may lead to complex fire behavior different from that in regular buildings. In this study, we focus on the impact of ventilation conditions and the status of doors in such buildings on fire evolution and smoke plume characteristics through experiments. The temperature variation in the fire room and corridor is measured under different ventilation power, ventilation time, and door opening width conditions. This shows that the width of the door has the greatest impact on fire development. A smaller gap in the door opening restricts air circulation between the interior and exterior of the room, resulting in a rapid decrease in the oxygen concentration within the fire room and a decrease in the combustion reaction rate of wood fires. The ventilation power exerts the most significant influence on the temperature variation in the corridor. These findings provide empirical data and a basis for fire science studies in high-altitude hermetic pressurized buildings and can guide existing fire protection design and management for improved safety.